Stringy Higgs Mechanizm and Fate of Open Strings - SHATASHVILI, SAMSON (My University, 2001)
We propose a refinement of the physical picture describing di fferent vacua in bosonic string theory. The vacua with closed strings and open string s are connected by the string field theory version of the Higgs mechanism, generalizing th e Higgs mechanism of an abelian gauge field interacting with a complex scalar. In accordance with Sen?s conjecture, the condensation of the tachyon is an essential part of the story . We consider this phenomenon from the point of view of both a world-sheet sigma-model and t he target-space theory. In the Appendix the relevant remarks regarding the choice of th e coordinates in the back- ground independent open string field theory are given
PUBLISHED
Keywords: Chemistry